Desigualdades persistentes, direitos e democracia contemporânea - Aloísio Ruscheinsky (Ciências Sociais Unisinos)
This paper addresses inequalities as historical constructions. It sees the disjunction between inequalities and rights as having continuity and discontinuity in economic, political, and cultural aspects. In this sense, despite social policies and the middle scale decision devices, the evaluation of the Gini coefficient shows a massive persistence of inequalities. On one hand, human rights had consolidated in Brazil through conflicts regarding democracy; on the other, there are still paradoxes on contemporary democracy, and this paper aims to show some obstacles for an adequate distribution of civil rights.